2022
DOI: 10.1101/2022.04.21.489075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent acute versus prolonged pharmacological GLP-1R responses in adult beta cell-selective β-arrestin 2 knockout mice

Abstract: The GLP-1R is a GPCR from the glucagon receptor family with important roles in the regulation of beta cell function and feeding behaviours. After ligand-stimulated G protein binding, active GLP-1Rs are rapidly desensitised by GRKs, followed by recruitment of β-arrestins, scaffolding proteins that terminate G protein interaction through steric hindrance but also act as independent signalling mediators. GLP-1R agonists (GLP-1RAs) are well-established therapeutics in type 2 diabetes and obesity that are neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 76 publications
(172 reference statements)
0
12
0
Order By: Relevance
“…However, β-cellspecific conditional knockout studies of β-arrestin-1 and -2 in mice showed no acute insulin secretory deficit in response to GLP-1R agonists, 41,42 although we recently found that loss of β-arrestin-2 may lead to reduced GLP-1R agonist-induced insulin secretion in female mice and DIO male mice, omitted from earlier studies. 43 With this in mind, we aimed to test whether partial or complete loss of GLP-1R agonist-induced β-arrestin recruitment is optimal for enhancing insulin secretion using SRB106 and SRB107 The rapid expansion of next-generation sequencing technology has highlighted extensive genomic coding variation in drug targets. 17 Current GLP-1R agonists are effective for many patients, but a significant minority fail to achieve treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…However, β-cellspecific conditional knockout studies of β-arrestin-1 and -2 in mice showed no acute insulin secretory deficit in response to GLP-1R agonists, 41,42 although we recently found that loss of β-arrestin-2 may lead to reduced GLP-1R agonist-induced insulin secretion in female mice and DIO male mice, omitted from earlier studies. 43 With this in mind, we aimed to test whether partial or complete loss of GLP-1R agonist-induced β-arrestin recruitment is optimal for enhancing insulin secretion using SRB106 and SRB107 The rapid expansion of next-generation sequencing technology has highlighted extensive genomic coding variation in drug targets. 17 Current GLP-1R agonists are effective for many patients, but a significant minority fail to achieve treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we again observe reduced propensity for b-arrestin 2 recruitment by the GIPR, this time in a beta cell context. The role of b-arrestins on incretin receptor trafficking and signaling has previously been investigated by us from several angles, for example by the use of biased agonists with different capabilities for b-arrestin recruitment [8,26], using in vivo conditional b-arrestin 2 knockout mouse models [21], or with in vitro cell systems with deleted b-arrestin 1/2 expression [13,26]. In all these instances, b-arrestin recruitment closely correlated with the degree of incretin receptor internalization, but alterations in b-arrestin expression levels or complete b-arrestin deletion did not lead to .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we again observe reduced propensity for β-arrestin 2 recruitment by the GIPR, this time in a beta cell context. The role of β-arrestins on incretin receptor trafficking and signaling has previously been investigated by us from several angles, for example by the use of biased agonists with different capabilities for β-arrestin recruitment [8, 26], using in vivo conditional β-arrestin 2 knockout mouse models [21], or with in vitro cell systems with deleted β-arrestin 1/2 expression [13, 26]. In all these instances, β-arrestin recruitment closely correlated with the degree of incretin receptor internalization, but alterations in β-arrestin expression levels or complete β-arrestin deletion did not lead to significant effects in receptor endocytosis, but rather resulted in the prolongation of cAMP/PKA signaling duration, suggesting that the main effect of this important signaling mediator lies in the steric hindrance caused by its binding to the receptor, leading to reduced access of Gα S to its binding pocket and promoting homologous receptor desensitization [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations